Simulation Study on Surface Temperature Distribution of Collector Strip Material Under Pantograph-Catenary Arc of Urban Rail - Xiaoying Yu; Mengjie Song; Ze Wang (IEEE Access, 2023)
With the increasing speed of urban rail trains, the vibration between the pantograph collector strip and the contact wire intensifies, and the pantograph-catenary arc occurs frequently, which severely wear the surface materials of the pantograph-catenary. The arc burning strength and arc extinguishing characteristics of the pantograph-catenary arc are affected by the arc temperature parameters. Based on the theory of magnetohydrodynamics, this paper establishes a mathematical model with multi-physical field coupling. According to the mathematical model, apply COMSOL finite element software to establish a simulation model for the arc of the urban rail pantograph-catenary, and simulate and analyze the temperature field about the arc. Use an experimental platform to simulate experiments and verify the feasibility of the simulation model. Based on the simulation model, the surface temperature distribution of different collector strip materials under the action of urban rail pantograph-catenary arc is studied. The research results indicate that there is a positive connection between the arc duration of urban rail pantograph-catenary and the maximum arc temperature; Although the collector strip materials are different, the surface temperature distribution of the collector strip is the same; The surface temperature of the collector strip decreases with the increase of the thermal conductivity of the collector strip material.